2016
DOI: 10.1371/journal.pone.0149924
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on Foot Loading Characteristics in Gait for Children Aged 1 to 12 Years

Abstract: BackgroundOverweight and obesity are increasing health problems that are not restricted to adults only. Childhood obesity is associated with metabolic, psychological and musculoskeletal comorbidities. However, knowledge about the effect of obesity on the foot function across maturation is lacking. Decreased foot function with disproportional loading characteristics is expected for obese children. The aim of this study was to examine foot loading characteristics during gait of normal-weight, overweight and obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 38 publications
4
54
0
4
Order By: Relevance
“…Evidences indicated that obesity could have negative effects on body stability, morphology of the locomotor system and plantar pressure (9). Thus, in addition to other reported metabolic and psychological consequences, musculoskeletal comorbidities are a frequent problem in overweight and obese children (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Evidences indicated that obesity could have negative effects on body stability, morphology of the locomotor system and plantar pressure (9). Thus, in addition to other reported metabolic and psychological consequences, musculoskeletal comorbidities are a frequent problem in overweight and obese children (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…12 Selain itu, status gizi overweight dan obesitas menunjukkan tingginya area kontak, rendahnya medial longitudinal arch, dan lebih besarnya tekanan pada kaki yang mengakibatkan banyaknya jumlah kondisi flat foot pada anak dengan status gizi overweight maupun obesitas. 16 Data dari peneliltian ini menunjukkan bahwa delapan dari lima belas (26,67%) anak yang mengalami flat foot memiliki riwayat anggota keluarga yang mengalami flat foot. Diantara anggota keluarga yang memiliki riwayat flat foot, persentasi kejadian flat foot pada ayah, ibu, dan saudara lainnya sebesar 16,67%, sedangkan untuk saudara kandung 5,56%.…”
Section: Pembahasanunclassified
“…It imposes functional restrictions on performing daily activities. It contributes to the reduction of the longitudinal and transverse arches, causing improper loading of the feet in terms of statics and dynamics [14][15].…”
Section: Introductionmentioning
confidence: 99%